2020
DOI: 10.1038/s41398-020-0710-4
|View full text |Cite
|
Sign up to set email alerts
|

Large epigenome-wide association study of childhood ADHD identifies peripheral DNA methylation associated with disease and polygenic risk burden

Abstract: Epigenetic variation in peripheral tissues is being widely studied as a molecular biomarker of complex disease and disease-related exposures. To date, few studies have examined differences in DNA methylation associated with attention-deficit hyperactivity disorder (ADHD). In this study, we profiled genetic and methylomic variation across the genome in saliva samples from children (age 7-12 years) with clinically established ADHD (N = 391) and nonpsychiatric controls (N = 213). We tested for differentially meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 78 publications
(96 reference statements)
2
80
0
Order By: Relevance
“…The second one found hypermethylated regions in genes involved in fatty acid metabolism and fatty acid oxidation pathways associated with ADHD persistence when compared to remittance 21 . In the childhood period, Wilmot et al analyzed a population cohort of school-age boys and found lower methylation levels at the VIPR2 gene in ADHD subjects compared to their age-and sex-matched controls 10 , results that were recently replicated in the largest EWAS on ADHD in children conducted so far 22 . In a similar aged population cohort, Walton et al investigated ADHD symptom trajectories from birth to adolescence and pointed to epigenetic marks in genes related to neural tube development and peroxisomal mechanisms as candidates to be involved in the different ADHD symptom trajectories across time 6 .…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…The second one found hypermethylated regions in genes involved in fatty acid metabolism and fatty acid oxidation pathways associated with ADHD persistence when compared to remittance 21 . In the childhood period, Wilmot et al analyzed a population cohort of school-age boys and found lower methylation levels at the VIPR2 gene in ADHD subjects compared to their age-and sex-matched controls 10 , results that were recently replicated in the largest EWAS on ADHD in children conducted so far 22 . In a similar aged population cohort, Walton et al investigated ADHD symptom trajectories from birth to adolescence and pointed to epigenetic marks in genes related to neural tube development and peroxisomal mechanisms as candidates to be involved in the different ADHD symptom trajectories across time 6 .…”
Section: Introductionmentioning
confidence: 96%
“…Studies of DNA methylation profiles in ADHD have been conducted using peripheral blood, cord blood, buccal samples or saliva 6,[9][10][11][20][21][22][23][24][25][26][27][28] . Candidate gene studies have revealed differential methylation patterns in genes involved in the dopaminergic, serotoninergic and neurotrophic systems, including SLC6A4, DRD4, COMT, ANKK1, BDNF, or NGFR, associated with ADHD symptomatology and severity [23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA methylation is highly dynamic during human brain development [84] and perturbations in DNA methylation are associated with several neurodevelopmental disorders, including ASD [85,86], schizophrenia [87] and ADHD [88], and have also been documented following PTB [22].…”
Section: Discussionmentioning
confidence: 99%